2021
DOI: 10.1007/s00268-020-05933-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and Risk Factors for Gastroepiploic Lymph Node Involvement in Patients with Cancer of the Transverse Colon Including the Hepatic Flexure

Abstract: Background To define the incidence of gastroepiploic lymph node (GLN) metastasis in patients with cancer of the transverse colon, including the hepatic flexure, and to identify the preoperative predictors of GLN involvement in a large‐volume center in China. Methods This retrospective monocentric cross‐sectional study respected the STROBE statement. Of 3208 consecutive patients who underwent colon cancer resection, a total of 371 patients with cancer of the transverse colon including the hepatic flexure who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…In cases with advanced colorectal tumors, it was clearly proven that excision of as many LN as possible is important at least for estimating survival and determining the indication for adjuvant cancer treatment [ 12 ]. In patients with colorectal cancer, successful resection of metastatic foci, such as those located in the lung or liver, is associated with significant long-term survival [ 13 ], and, as a consequence, the resection of non-regional LN metastases in high risk patients [ 14 ] should be associated with an OS benefit. This is particularly significant in our country, as most colorectal tumors are still diagnosed in advanced stages, leading to a death count of 34/100,000 (recorded in 2016–2018), almost twofold higher than the average European range [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases with advanced colorectal tumors, it was clearly proven that excision of as many LN as possible is important at least for estimating survival and determining the indication for adjuvant cancer treatment [ 12 ]. In patients with colorectal cancer, successful resection of metastatic foci, such as those located in the lung or liver, is associated with significant long-term survival [ 13 ], and, as a consequence, the resection of non-regional LN metastases in high risk patients [ 14 ] should be associated with an OS benefit. This is particularly significant in our country, as most colorectal tumors are still diagnosed in advanced stages, leading to a death count of 34/100,000 (recorded in 2016–2018), almost twofold higher than the average European range [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, GCLN metastasis was identified as an independent prognostic factor for patients with TCC [ 25 ]. The question that rises is whether all patients with TCC should have an extended lymphadenectomy, or the identification of preoperative risk factors of GCLN involvement could guide indication for extended lymphadenectomy [ 9 , 14 , 24 ]. From the oncologist’s point of view, a completely resected TNM stage IV benefits from the same adjuvant chemotherapy as a locally advanced TNM stage III, which is up to 6 months of perioperative treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…identified the small blood and lymphatic vessels connecting the transverse colon and the greater omentum and connecting the transverse colon and the pancreas, which may be the potential pathways for lymphatic metastasis to infrapyloric and gastroepiploic lymph nodes (IGLN) ( 33 ). Previous studies reported 0.7-22% incidence rates of IGLN metastases for right-sided colon cancer ( 34 42 ). In addition, the rates of IGLN metastases were higher (1.7-33%) in patients with positive mesocolic nodes ( 32 ).…”
Section: Discussionmentioning
confidence: 95%
“…There is no recommendation in current guidelines about IGLN routine dissection for hepatic flexure/transverse colon tumours. Few authors have reported IGLN metastases rates from colonic tumours (range 0.7%-22.0%) [4][5][6][7][8][9][10][11]. Routine IGLN dissection could increase morbidity and mortality [5].…”
Section: Laparoscopic Complete Mesocolic Excision With Extended D3 Ly...mentioning
confidence: 99%